PENGARUH FLY ASH DENGAN PENAMBAHAN CACAHAN KARET, SILICA FUME DAN SUPERPLASTICIZER TERHADAP BETON - Redaksi Tim Jurnal (FORUM MEKANIKA, 2018)
Along with the progress of environmental action movement, the systematic destruction of nature, began to be reduced, so it is necessary to think about the use of new types of mixed sources that can be used in the manufacture of concrete. Utilization of fly ash and rubber debris on concrete is expected to cope with the impact of environmental pollution. Therefore, the effect of variations of fly ash with the addition of rubber shards and with added materials (admixture) such as silica fume and superplasticizer on concrete mixes can improve the quality of concrete. The samples of the study were made by comparison of fly ash Bangka with fly ash Suralaya by 0%, 10% of the weight of cement and 5% of fine weight aggregate with silica fume 4% of the weight of cement that has been reduced by the weight of fly ash and supplemented by a superplasticizer of 2% water needs. Testing sample at age 7, 14, 28 days, to know compressive strength, slump and concrete timesetting.